Effects of tartaric acid contents on phase homogeneity, morphology and properties of poly (butyleneadipate-co-terephthalate)/thermoplastic starch bio-composities. (July 2019) - Zhang, Shuidong; He, Yan; Lin, Zesheng; Li, Jun; Jiang, Guo
Abstract: Poly (butyleneadipate-co-terephthalate)/thermoplastic starch with high performances was a candidate alternative for polyethylene. In this study, starch, glycerol and tartaric acid (TA) were extruded to fabricate thermoplastic starch/TA (TPS-TA) firstly, then re-extruded with PBAT to achieve PBAT/TPS-TA composites. Effects of TA contents on the structure of TPS, the phase morphology and performances of PBAT/TPS-TA were evaluated by Fourier transform infrared spectroscopy (FT-IR), dynamic thermomechanical analysis (DMA), scanning electron microscopy (SEM), viscosity, dynamic rheological and in vitro biodegradation measurement, contact angle and tensile test, respectively. When its content ranged from 0.5 to 1%, TA acted as acid catalyst to reduce the molecular weight of starch and shear viscosity of TPS, meanwhile, served as coupling reagent to improve the compatibility of TPS and PBAT matrix. Consequently, TPS-TA particles uniformly dispersed in PBAT matrix with 0.18 μm diameter and PBAT/TPS-TA could achieve the homogeneous phase and improved tensile properties. However, when TA content was higher than 1%, the excessive TA would decrease the interface interaction and caused the morphology of PBAT/TPS-TA to reverse from homogeneous phase to "sea-island structure". This study paved the way for fabricating low-cost PBAT/TPS-TA with 15 times and 40% increments in biodegradation rate and ductility, respectively, when PBAT was used as the control. Highlights: TA acts diverse role in the PBAT/TPS-TA composites, such as acid catalyst and coupling effect, depending on the content. The biodegradation rate of PBAT/TPS-TA composites increased by 15%, 14 times higher than that of PBAT. TA elevates the compatibility of TPS and PBAT, reverses the composites from "sea-island structure" phase to homogeneity. The incorporated TA promotes the melt flowability of TPS and decreases the diameter of TPS-TA particles to 0.18 μm. The most important effect of TA on the properties of TPS-TA is it reduces the Mv of starch and shear viscosity of TPS.